2017
DOI: 10.1016/j.celrep.2017.10.114
|View full text |Cite
|
Sign up to set email alerts
|

The Aryl Hydrocarbon Receptor Preferentially Marks and Promotes Gut Regulatory T Cells

Abstract: SUMMARY Local environment may impact the development and function of tissue-resident T regulatory cells (Tregs) that are crucial for controlling inflammation. Although the aryl hydrocarbon receptor (Ahr), an environmental sensor, is expressed by Tregs, its role in Treg cell development and/or function remains elusive. Here, we generated mouse genetic models to ablate or activate Ahr expression specifically in Tregs. We showed that Ahr was expressed more abundantly by peripherally induced Treg (pTregs) in the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
134
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(145 citation statements)
references
References 68 publications
10
134
0
1
Order By: Relevance
“…Previous studies have shown that gut colonization by specific microbial communities causes induction and expansion of Foxp3 + Treg cells in the intestinal and systemic compartments . Further, gut bacteria play a critical role in maintaining peripheral tolerance and gut immune homeostasis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that gut colonization by specific microbial communities causes induction and expansion of Foxp3 + Treg cells in the intestinal and systemic compartments . Further, gut bacteria play a critical role in maintaining peripheral tolerance and gut immune homeostasis .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that gut colonization by specific microbial communities causes induction and expansion of Foxp3 + Treg cells in the intestinal and systemic compartments. [43][44][45] Further, gut bacteria play a critical role in maintaining peripheral tolerance and gut immune homeostasis. 46,47 Our results show that depletion of gut bacteria using broad-spectrum antibiotics diminishes Foxp3 + T-cell frequency, compared with mice with an intact gut microbiota, but less significantly in YBGtreated mice compared with their control counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that gut colonization by specific microbial communities causes induction and expansion of Foxp3+ Tregs in the intestinal and systemic compartments [44][45][46] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these polysaccharides are being considered as prebiotics with the ability to promote growth of specific beneficial microbial communities. Previous studies have shown that gut colonization by specific commensal microbial communities causes induction and expansion of Foxp3+ Tregs in the intestinal and systemic compartments (47)(48)(49). Further, gut bacteria play a critical role in maintaining peripheral tolerance and gut immune homeostasis (50,51).…”
Section: Discussionmentioning
confidence: 99%